A step toward bio-inspired dental composites - Tiu, Janine; Belli, Renan; Lohbauer, Ulrich (Biomaterial Investigations in Dentistry, 2023)
This feasibility study aimed to develop a new composite material of aligned glass flakes in a polymer resin matrix inspired by the biological composite nacre. The experimental composite was processed by an adapted method of pressing a glass flake and resin monomer system. By pressing and allowing the excess monomer to flow out, the long axis of the flakes was aligned. The resultant anisotropic composite with silanized and non-silanized glass flakes were subjected to fracture toughness tests. We observed increasing fracture toughness with increasing crack extension (Δa) known as resistance curve (R-curve) behavior. Silanized specimens had higher stress intensity KR-Δa over non-silanized specimens, whereas non-silanized specimens had a much lower Young's modulus, and higher nonlinear plastic-elastic JR-Δa R-curve. In comparison with conventional composites, flake-reinforced composites can sustain continued crack growth for more significant extensions. The primary toughening mechanism seen in flake-reinforced composites was crack deviation and crack branching. We produced an anisotropic model of glass flake-reinforced composite showing elevated toughening potential and a prominent R-curve effect. The feasibility of flake reinforcement of dental composites has been shown using a relatively efficient method. The use of a biomimetic, nacre-inspired reinforcement concept might guide further research toward improvement of dental restorative materials.
EVALuna2:560302
Keywords: Composite materials; biomaterials; dentalmaterials; mechanicalproperties; bioinspiration; R-curve

Characterization of heat-polymerized monomer formulations for dental infiltrated ceramic networks - Tiu, Janine; Belli, Renan; Lohbauer, Ulrich (Applied Sciences, 2021)
(1) Objectives: This work examined properties of dental monomer formulations of an aromatic dimethacylate (BisGMA), aliphatic urethane dimethacrylate (UDMA), and triethylene glycol dimethacrylate (TEGDMA). The monomers were combined in different ratio formulations and heat-polymerized containing the initiator benzoyl peroxide (BPO) specifically for the purpose of infil-tration into polymer-infiltrated composite structures. (2) Methods: The monomers were combined in different weight ratios and underwent rheological analysis (viscosity and temperature dependence), degree of conversion, and mechanical properties (elastic modulus, hardness, fracture toughness). (3) Results: Rheological properties showed Newtonian behavior for monomers with a large dependence on temperature. The addition of BPO allowed for gelation in the range of 72.0–75.9◦ C. Degree of conversion was found between 74% and 87% DC, unaffected by an increase of TEGDMA (up to 70 wt%). Elastic modulus, hardness, and fracture toughness were inversely proportional to an increase in TEGDMA. Elastic modulus and hardness were found slightly increased for UDMA versus BisGMA formulations, while fracture toughness ranged between 0.26 and 0.93 MPa.m0.5 for UDMA-and 0.18 and 0.68 MPa.m0.5 for BisGMA-based formulations. (4) Significance: Heat-polymerization allows for greater range of monomer formulations based on viscosity and degree of conversion when selecting for infiltrated composite structures. Therefore, selection should be based on mechanical properties. The measured data for fracture toughness combined with the reduced viscosity at higher UDMA:TEGDMA ratios favor such formulations over BisGMA:TEGDMA mixtures.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Heat polymerization; Mechanical properties; Methacrylate monomer; Resin infiltration

Contemporary CAD/CAM Materials in Dentistry - Tiu, Janine; Belli, Renan; Lohbauer, Ulrich (Current Oral Health Reports, 2019)
Purpose of Review: To present an update on the current CAD/CAM materials in restorative dentistry. Recent Findings: Important contributions are seen in updated mechanical properties of CAD/CAM materials, new insights in lithium silicate systems, and development in translucent zirconia. Many materials are arriving at optimized processing procedures and further development will come from new strategies and systems. Increasing our understanding of CAD/CAM materials will improve their use and indications and drive innovation. Summary: A general update was provided by classifications, mechanical properties, and clinical considerations by providing commentary on recent significant contributions.
CRIS-Team Scopus Importer:2021-04-20
Keywords: CAD/CAM; Dental restorative materials; Glass-ceramics; Mechanical properties; Zirconia

R-curve behavior of a short-fiber reinforced resin composite after water storage - Tiu, Janine; Belli, Renan; Lohbauer, Ulrich (Journal of the Mechanical Behavior of Biomedical Materials, 2020)
As a supplement to our investigation into R-curves in a short-fiber reinforced dental resin composite, we investigate the effects of 2-months water storage. Water is known to degrade the siloxane bonds linking matrix and fillers, which has been suggested to decrease the fracture toughness in conventional resin composites. However, fiber-reinforced systems seem to be less affected as the toughness is dependent on fiber bridging, which is only effective if a weaker interfacial bond between fiber and matrix is present.
CRIS-Team Scopus Importer:2020-02-21

Rising R-curves in particulate/fiber-reinforced resin composite layered systems - Tiu, Janine; Belli, Renan; Lohbauer, Ulrich (Journal of the Mechanical Behavior of Biomedical Materials, 2020)
Background: An anisotropic fracture behavior has already been successfully induced in a condensable resin composite by reinforcement with discontinuous glass fibers, developing a steep rise in the fracture resistance curve. There is still the need for developing such concepts further, by evaluating the behavior of layered structures that attempt to replicate the natural gradient structure of enamel and dentin. Methods: Monolithic and bilayer specimens of a flowable short-fiber particulate-reinforced composite (SFPRC) material (GC Corp.) and a commercial flowable particulate-reinforced composite (PRC) (Essentia HiFlo, GC Corp.) were produced with the fibers aligned perpendicular or randomly oriented to the plane of crack propagation. Pre-cracked specimens were tested in 3-point bending using the single-edge-V-notch-beam method with accurate displacement tracking recordrecord. Controlled crack growth experiments were conducted at progressive crack extension intervals to build R-curves using linear-elastic and elastic-plastic fracture mechanics. Results: We demonstrate firsthand the development of R-curves in resin composite bilayers, with crack arrest at the interface and a steep rise in crack resistance with subsequent drop within the SFPRC layer. Crack deflection and fiber bridging were found to contribute to a higher rise in the R-curves for specimens with aligned fibers; still, randomly oriented fibers showed significant R-curve development, especially at short range intervals. An increase in the vol% of fibers and a decrease in the Young's modulus contributed to a higher overall performance of the flowable vs. the condensable SFPRF materials. Conclusions: SFPRC materials show an up to 5-fold improvement in the fracture resistance over conventional PRCs, and show the potential to be used to build gradient structures by varying the fiber alignment and fibers parameters (length and packing).
CRIS-Team Scopus Importer:2019-11-29
Keywords: Dental; Fracture toughness; Glass fiber; R-curve; Resin composite; Restorative materials

Thickness influence of veneering composites on fiber-reinforced systems. - Tiu, Janine; Belli, Renan; Lohbauer, Ulrich (Dental Materials, 2021)
OBJECTIVE: Short fiber reinforced composites (SFRC) require a veneering layer of conventional composite when used as restorations in the oral environment. The current study investigates the toughening effects during the path of a preexisting crack propagating through the bilayer system as it confronts the interface, through the attempted alignment of fibers and matrix-fiber interactions in the SFRC, and the distance it travels in the SFRC. METHODS: Bilayer systems of SFRC and conventional composite were produced with aligned fibers perpendicular to load direction. Single-edge-notched bend (SENB) specimens (25 × 5 × 2.5 mm3) with pre-crack length (a) to width (W) ratios (a/W = 0.2-0.8) were produced and tested in 3-point bending configuration until complete fracture. The specific work of fracture (we) was deduced from calculating the area under the load-displacement curves. Fiber alignment was digitally evaluated from images taken from the top and side planes of the specimen. RESULTS: The toughness of the bilayer system is optimal when maximum SFRC thickness is used. EWF methods showed toughness and increasing nonessential work of fracture scaling with ligament length. A longer distance is accompanied by a higher distribution of aligned fibers bridging behind the crack wake, reducing crack driving forces at the crack tip. SIGNIFICANCE: SFRC materials provide increasing toughening potential with increasing thickness, and have the ability to be more anisotropic than other composite materials. Clinically, the layer must have a conventional composite cover layer, but which thickness does not affect toughness potential. Therefore the thickness of the conventional composite can be dictated by wear behavior.
EVALuna2:465659